Sublethal whole-body irradiation causes progressive premature frailty in mice. (June 2019) - Fielder, Edward; Weigand, Melanie; Agneessens, Julien; Griffin, Brigid; Parker, Craig; Miwa, Satomi; von Zglinicki, Thomas
Highlights: Mice that survive irradiation develop progressive frailty. Irradiation-induced premature frailty is phenotypically equal to frailty in old animals. Premature frailty is associated with mortality and low cognition. Sub-lethal whole body irradiation may constitute a good mouse model to test efficiency of anti-ageing interventions. Abstract: There is an unmet need to develop and validate therapies that can treat or at least prevent premature therapy-induced frailty, multi-morbidity and mortality in long-term tumour survivors. In an approach to develop a first mouse model for therapy-induced long-term frailty, we irradiated male C57Bl/6 mice at 5–6 months of age sub-lethally with 3 × 3 Gy (whole body) and assessed subsequent frailty for up to 6 months using a Rockwood-type frailty index (FI). Frailty scorers were trained to obtain excellent inter- and intra-observer reproducibility. Irradiated mice developed progressive frailty approximately twice as fast as controls. This was premature frailty; it was phenotypically identical to that in non-irradiated mice at higher age. As expected, frailty was associated with decreased cognition and predicted mortality. In irradiated mice, frailty and neuromuscular performance, measured by Rotarod and Hanging Wire tests, were not associated with each other, probably because of long-term decreased body weights after irradiation. We conclude that progressive frailty following sub-lethal irradiation comprises a sensitive and easy to use test bed for interventions to stop premature ageing in long-term tumour survivors.